Kalix: A Java 11 Library for Developing Eclipse Arrowhead System-of-Systems - Palm, Emanuel; Bodin, Ulf; Schelen, Olov (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2020)
Eclipse Arrowhead, an upcoming open source framework for designing cyber-physical system-of-systems, is starting to become complete enough to be the subject of serious evaluation and prototyping. As a consequence, it has become increasingly pertinent to provide software that makes it straightforward to use and learn it. To address this, we here present Arrowhead Kalix, a Java 11 library designed for the efficient and effective development of correct, concise and relatively performant Arrowhead-compliant systems. In this paper, we outline the philosophy behind the design of the library, its architecture, its fundamental components and give some examples of how it can be used. The purpose of the paper is both to educate and to provide academics using Kalix with a credible point of reference.